δ-fuzzy Ideals in MS-algebras - Berhanu Assaye Alaba; Mihret Alamneh Taye; Teferi Getachew Alemayehu (International Journal of Mathematics And its Applications, 2018)
In this paper, we introduce the concept of δ -fuzzy ideals and α -level principal δ -fuzzy ideals in an MS-algebra and study basic properties of these ideals with respect to homomorphisms. It is observed that the class of all δ -fuzzy ideals forms a complete distributive lattice and the class of all α -level principal δ -fuzzy ideals forms a de Morgan algebra. A characterization of δ -fuzzy ideals in terms of α -level principal δ -fuzzy ideals is given.